New and Updated Recommendations for the Treatment of Juvenile Idiopathic Arthritis–Associated Uveitis and Idiopathic Chronic Anterior Uveitis. Issue 5 (10th January 2023) - Foeldvari, Ivan; Maccora, Ilaria; Petrushkin, Harry; Rahman, Najiha; Anton, Jordi; de Boer, Joke; Calzada‐Hernández, Joan; Carreras, Elisa; Diaz, Jesus; Edelsten, Clive; Angeles‐Han, Sheila T.; Heiligenhaus, Arnd; et al.
Abstract : Objective: The Multinational Interdisciplinary Working Group for Uveitis in Childhood identified the need to update the current guidelines, and the objective here was to produce this document to guide clinicians managing children with juvenile idiopathic arthritis–associated uveitis (JIAU) and idiopathic chronic anterior uveitis (CAU). Methods: The group analyzed the literature published between December 2014 and June 2020 after a systematic literature review conducted by 2 clinicians. Pediatric rheumatologists were paired with ophthalmologists to review the eligible 37 publications. The search criteria were selected to reflect those used for the 2018 Single Hub and Access point for pediatric Rheumatology in Europe (SHARE) recommendations, in order to provide an update, rather than a replacement for that publication. The summary of the current evidence for each SHARE recommendation was presented to the expert committee. These recommendations were then discussed and revised during a video consensus meeting on January 22, 2021, with 14 voting participants, using a nominal group technique to reach consensus. Results: JIAU treatment was extended to include CAU. Fourteen recommendations regarding treatment of JIAU und CAU with >90% agreement were accepted. Conclusion: An update to the previous 2018 SHARE recommendations for the treatment of children with JIAU with the addition of CAU was created using an evidence‐based consensus process. This guideline should help support clinicians to care for children and young people with CAU.